Health-related quality of life among patients with symptomatic carotid disease. Issue 1047 (5th October 2012) - Vlajinac, Hristina; Marinkovic, Jelena; Maksimovic, Milos; Kocev, Nikola; Vasiljevic, Nadja; Backovic, Dusan; Radak, Djordje
Abstract : Objectives: To evaluate health-related quality of life (HRQoL) in patients with symptomatic carotid disease (amaurosis fugax, transient ischaemic attack, stroke); to compare it with that of the general population; to explore whether HRQoL depends on the severity of the disease and to investigate the possible association between some demographic and clinical characteristics of patients and HRQoL. Methods: This cross-sectional study involved 175 patients with symptomatic carotid atherosclerotic disease who were referred for endarterectomy between January 2011 and December 2011. HRQoL was measured using Medical Outcome Survey Short Form 36 (SF-36). Results: In comparison to both referent populations, patients with carotid disease had significantly lower mean SF-36 scores for role-physical (41.6 vs. 61.5 and 67.8), social functioning (65.4 vs. 73.8 and 80.0), role-emotional (48.2 vs. 68.6 and 80.5) and mental health (51.5 vs. 61.9 and 66.0). The SF-36 scores were significantly lower in female patients with carotid disease than in men (for role-physical 32.3 vs. 46.5; for bodily pain 57.0 vs. 73.0; for general health 55.6 vs. 61.5; for vitality 55.4 vs. 60.1; for social functioning 57.1 vs. 69.8 and for role-emotional 37.2 vs. 54.1). Significantly lower SF-36 scores were also found in patient with comorbidity (for physical functioning 68.1 vs. 77.7; for role-physical 35.1 vs. 52.3; for bodily pain 62.6 vs. 75.4; for general health 56.8 vs. 63.8; for social functioning 61.9 vs. 71.0, for role-emotional 41.6 vs. 59.1and for mental health 52.5 vs 49.8). In a multivariable analysis, education, occupation, body mass index, metabolic syndrome and severity of the disease had a weak influence on patients' HRQoL, while age, marital status, smoking, alcohol consumption, physical activity and the degree of carotid stenosis had no effect on patients' HRQoL. The SF-36 scores did not substantially change after adjustment for confounding variables. Conclusions: Patients with symptomatic carotid disease had poorer HRQoL, especially its mental components, than the general population. The severity of the disease was significantly associated only with the SF-36 role-physical subscale. HRQoL in patients with symptomatic carotid disease was poorer in women than in men, and was not affected by age and other demographic and clinical characteristics of patients.